2010
DOI: 10.1161/circresaha.109.203828
|View full text |Cite
|
Sign up to set email alerts
|

Structural Heterogeneity in the Ventricular Wall Plays a Significant Role in the Initiation of Stretch-Induced Arrhythmias in Perfused Rabbit Right Ventricular Tissues and Whole Heart Preparations

Abstract: Rationale: Mechanical stress is known to alter the electrophysiological properties of the myocardium and may trigger fatal arrhythmias when an abnormal load is applied to the heart. Objective: We tested the hypothesis that the structural heterogeneity of the ventricular wall modulates globally applied stretches to create heterogeneous strain distributions that lead to the initiation of arrhythmias. Methods and Results: We applied global stretches to arterially perfused rabbit right ventricular tissue preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Seo et al 16 recently employed a marker tracking scheme together with optical mapping to estimate strain distributions and track electrical propagation in cardiac preparations. For each video frame, they used a cross correlation technique similar to ours to find the displacements of epicardial markers relative to a reference video frame.…”
Section: Comparison To Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seo et al 16 recently employed a marker tracking scheme together with optical mapping to estimate strain distributions and track electrical propagation in cardiac preparations. For each video frame, they used a cross correlation technique similar to ours to find the displacements of epicardial markers relative to a reference video frame.…”
Section: Comparison To Other Methodsmentioning
confidence: 99%
“…They used the method to relate deformation to arrhythmia initiation. 16 In our method, ring-shaped material markers are attached to the isolated heart, which is stained with voltage sensitive dye (VSD). V m signals are obtained by recording the fluorescence emitted from within each marker and using a ratiometric technique to minimize motion artifact.…”
Section: Introductionmentioning
confidence: 99%
“…One concern regarding single cell experiments is that techniques for stretching isolated adult cardiomyocytes are technically quite difficult, and coupling these techniques with electrophysiological study present a difficult hurdle [110]. Depending on the scientific question, there is interest in testing isolated adult cells as singles, doublets, or as slices or strips of tissue [88,[111][112][113]] Still, precise but population-level electrophysiological studies of electrically coupled cells under precise and physiological mechanical strain conditions remains challenging.…”
Section: The Need For Multicellular Tissue-scale Experimentsmentioning
confidence: 99%
“…A local stretch therefore can alter the local pathways of activation (Dhein et al, 2014). On the other hand, it has been shown that structural heterogeneities can affect stretch-induced ventricular arrhythmia (Seo et al, 2010). Wall thickness can be heterogeneously distributed over the ventricle, which will result in a regional modulation of a mechanical stimulus so that regional strain varies.…”
Section: Arrhythmogenesismentioning
confidence: 99%